سکوتِ اجباری کے معاشرتی نقصانات اور اسلامی نقطہ نظر: SOCIAL HARMS OF FORCED SILENCE AND ISLAMIC PERSPECTIVE (Al-Aasar, 2025)
Freedom of expression is an inborn quality and a gifted right from God, granted to every individual at birth. Every living creature has the right to express their pain and needs for the fulfillment of healthy survival. The language of these demands may vary, but the core concept of this freedom is the "Respect of Being" – being human, being alive, sacred, important, and useful. There are many ways to express oneself for enjoying rights and fulfilling obligations, though this freedom has its boundaries. However, forcibly silencing an opponent in order to manipulate the situation for one’s own interests should be discouraged in every religion, law, and society. Whenever humanity cries out in the distress of deprivation, it signals the presence of a notorious force of injustice. This act of suppression births “cruelty,” the weapon used by powerful entities to silence others. Societies where voices are suffocated cannot produce productive minds, indirectly putting them in a disadvantage in the rapidly evolving modern world. Religions, governance, and societies based on justice and equality provide defensive opportunities for sustaining a healthy and successful life. That is why “Islam” was bestowed by God as the final shelter of peace, as demonstrated by the last prophet (PBUH). Islam begins its training by molding the inner self, beliefs, ideology, and thinking, expanding its influence from the individual to the family, balanced society, welfare state, and ultimately, to a peaceful world.